PENGARUH HARGA DAN KUALITAS PELAYANAN PRODUK TERHADAP KEPUASAN KONSUMEN ( PADA TOKO TOP JAYA MOTOR BEKASI) - Tommy Fernandus; Syahrul Reza (JAMBIS : Jurnal Administrasi Bisnis, 2021)
This study aims to determine price and service quality on consumer satisfaction (atToko Top Jaya Motor Bekasi). This study uses quantitative methods. The data collectiontechnique used is a questionnaire. The population of this research is all buyers/consumers ofTop Jaya Motor Stores who buy Honda auto parts. The sampling technique used in this studywas simple random sampling with a population sampling method. The sample is 110 samples,the data analysis used is multiple linear regression analysis using the help of IBM Statisticssoftware version 26. The effect of price on consumer satisfaction at the Top Jaya Motor Storeis based on the correlation coefficient (R) of 0.884. The value of R2is between 0.75-0.99, sothe relationship between price and business development can be very strong. The effect ofservice quality on customer satisfaction at Toko Top Jaya Motor based on the correlationcalculation with a correlation coefficient value (R) of 0.675 is between 0.75-0.99, so therelationship between service quality and business development can be measured be said to bevery strong.